Soo Mann Sian receives the Vice-Chancellor Award, gift for parents - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 17 March 2022 - It must be the dream of every graduand to attend the Convocation Ceremony after years of studying and receive an award at the 15th UMP Convocation Ceremony.